Genetics of Gland-in-situ or Hypoplastic Congenital Hypothyroidism in Macedonia - Zdraveska, Nikolina; Kocova, Mirjana; Nicholas, Adeline K.; Anastasovska, Violeta; Schoenmakers, Nadia (Frontiers in Endocrinology, 2020)
Neonatal screening in Macedonia detects congenital hypothyroidism (CH) with an incidence of 1 in 1585 and more than 50% cases exhibit a normally-located gland-in-situ (GIS). Monogenic mutations causing dyshormonogenesis may underlie GIS CH; additionally, a small proportion of thyroid hypoplasia has a monogenic cause, such as TSHR and PAX8 defects. The genetic architecture of Macedonian CH cases has not previously been studied. We recruited screening-detected, non-syndromic GIS CH or thyroid hypoplasia cases (n=40) exhibiting a spectrum of biochemical thyroid dysfunction ranging from severe permanent to mild transient CH and including 11 familial cases. Cases were born at term, with birth weight >3000g and thyroid morphologies included goitre (n=11), thyroid hypoplasia (n=6) and apparently normal-sized thyroid. A comprehensive, phenotype-driven, Sanger sequencing approach was used to identify genetic mutations underlying CH, by sequentially screening known dyshormonogenesis-associated genes and TSHR in GIS cases and TSHR and PAX8 in cases with thyroid hypoplasia. Potentially pathogenic variants were identified in fourteen cases of which four were definitively causative; we also detected digenic variants in three cases. Seventeen variants (nine novel), were identified in TPO (n=4), TG (n=3), TSHR (n=4), DUOX2 (n=4), and PAX8 (n=2). The relatively low mutation frequency suggests that factors other than recognized monogenic causes (oligogenic variants, environmental factors or novel genes) may contribute to GIS CH in this region. Future non-hypothesis driven, next generation sequencing studies are required to confirm these findings.